The Influence of Investment Decisions, Funding Decisions, and Dividend Policies on Corporate Values in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange for the 2012-2016 - Jones Xaverius Pontoh; Agnes Punu (AIBPM Publisher, 2018)
The purpose of this study was to determine the effect of investment decisions, funding decisions, and dividend policies on firm value. The population in this study is a consumer goods manufacturing sector manufacturing company listed on the Indonesia Stock Exchange in 2012-2016. Data collection techniques in this study are panel data techniques, namely time series and cross section . The results showed that investment decisions have a positive and insignificant effect on firm value, funding decisions have a significant positive effect on firm value, and dividend policy has a negative and not significant effect on firm value. Keywords: Company Value, Investment Decision, Funding Decision and Dividend Policy.